Pengembangan Media Pembelajaran Gamifikasi Berbasis Web Untuk Materi Input-Process-Output Dan Arsitektur Komputer Von Neumann Pada Informatika Kelas X - Nur Kholis Wakhid; Ramadhan Cakra Wibawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Learning Input-Process-Output (IPO) and Von Neumann computer architecture is often challenging for tenth-grade students due to its abstract nature. This study aimed to develop a web-based gamified learning media for Informatics Grade X using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The media, named ArchiLogic, integrates gamification elements such as points, levels, leaderboards, and problem-based learning missions. Feasibility was assessed through expert validation: media experts gave a score of 90% and learning experts gave 92.14%, both categorized as "Very Feasible". Effectiveness was tested on 35 Grade X students at SMK Negeri 1 Lamongan using a one-group pretest-posttest design. Average scores improved from 46.34 (pretest) to 87.11 (posttest). The Paired Sample t-Test showed a significant difference (p-value < 0.001), and the N-Gain score reached 0.758 (High category). These results confirm that web-based gamification effectively facilitates better conceptual understanding and increases active student engagement in Informatics.